The Reed Smoot hearings: the investigation of a Mormon senator and the transformation of an American religion - Paulos, Michael Harold, editor; Hansen, Konden Smith, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2021)
Examines the hearings that followed Mormon apostle Reed Smoot's 1903 election to the US Senate and subsequent protests and petitioning efforts from mainstream Christian ministries disputing Smoot's right to serve. Explores how religious and political institutions adapted in response to societal and ecclesiastical trends.--Provided by publisher.
The Reed Smoot hearings and the theology of politics: perceiving an 'American' identity / Konden Smith Hansen -- "Justice is never permanently defeated anywhere": Reed Smoot's confirmation vote in the United States Senate / Michael Harold Paulos -- Anti-polygamy, the Constitution, and the Smoot hearings / Byron W. Daynes and Kathryn M. Daynes -- Do I hear an echo?: the continuing trial of the Mormon Church after Smoot's retention / Kenneth L. Cannon II -- My darling Allie, your Reed: letters 1903-1907 / Kathryn Smoot Egan -- Under the gun at the Smoot hearings: Joseph F. Smith's testimony / Michael Harold Paulos -- "Some divine purpose": Carl A. Badger and the Reed Smoot hearings / Gary James Bergera -- "A systematic, orderly, and unusually intelligent fight": Senator Fred T. Dubois and Reed Smoot / John Brumbaugh -- Appendix: LDS officials involved with new plural marriages from September 1890 to February 1907 / D. Michael Quinn.
Keywords: Smoot, Reed, 1862-1941 -- Political and social views; Mormons -- Political activity -- Utah -- History -- 20th century; Mormon Church -- United States -- History -- 20th century; Mormons -- Civil rights -- United States -- History -- 20th century; Religion and politics -- United States -- History -- 20th century; Legislators -- Utah -- History -- 20th century; Legislative hearings -- United States; Polygamy -- United States